An Unusual Case of Foreign Body Lodged in the Laryngopharynx of Neonate with Esophageal Atresia - Rahul Gupta; Manisha Saxena; Rozy Paul; Sharan Gubbi; Praveen Mathur (EL-Med-Pub, 2015)
A blunt‑tipped red rubber catheter is used to confirm the presence of esophageal atresia in any newborn with drooling of saliva and frothing from the mouth. Failure to pass it beyond 10cms into the esophagus is considered diagnostic. We here in report an extremely rare case of broken tip of red rubber catheter lodged in the laryngopharynx of 2-day-old neonate of esophageal atresia with distal tracheoesophageal fistula. During endotracheal intubation foreign body was accidentally removed.